Acute Traumatic Patellar Tendon Rupture at the Tibial Tuberosity Attachment without Avulsion Fracture - Shuichi Miyamoto; Makoto Otsuka; Fumio Hasue; Takayuki Fujiyoshi; Koushirou Kamiya; Hitoshi Kiuchi; Ken Ohara; Atsushi Yunde; Yasunori Toki; Tadashi Tanaka; Junichi Nakamura; Seiji Ohtori (Case Reports in Orthopedics)
Patellar tendon rupture in children is especially rare. The fact that the area of traumatic rupture has wide variations makes surgical treatment difficult. We present an 11-year-old boy with acute traumatic patellar tendon rupture at the tibial tuberosity attachment without avulsion fracture. Primary end-to-end repair and reinforcement using 1.5 mm stainless steel wires as a surgical strategy were undertaken. Early range of motion began with a functional knee brace and the reinforced stainless wire was removed 3 months after surgery. Knee function at the final follow-up was satisfactory. We suggest that this strategy may provide a useful option for surgical treatment.